Plasmacytoid urothelial carcinoma of the bladder: a case report - Aldousari, Saad (BioMed Central, 2009)
Plasmacytoid bladder cancer is a rare variant of transitional cell carcinoma. A 57-year-old man was referred to our institution for management of invasive transitional cell carcinoma diagnosed at a peripheral hospital. His complaints were of vague lower abdominal pain with associated urgency and frequency requiring oxybutynin. Metastatic workup was negative and was subsequently scheduled for a radical cystectomy. Routine colonoscopy 3 weeks prior to surgery was negative. Intraoperatively, he was found to have metastatic urothelial cancer involving the cecum and multiple metastatic deposits within the mesentery of the small intestines. He underwent a palliative cystectomy with ileal conduit formation. Final pathology revealed metastatic plasmacytoid variant of urothelial cancer. Histology and immunohistochemistry were compatible with plasmacytoid variant of urothelial cancer. Here we present our case of this rare variant of urothelial cancer with a review of its characteristics.